Gasification of indole in supercritical water: Nitrogen transformation mechanisms and kinetics. (28th September 2016) - Liu, Shanke; Jin, Hui; Wei, Wenwen; Guo, Liejin
Abstract: Nitrogen is an important element related to coal conversion process due to its considerable impact on the environment. In this study, indole, a nitrogen-containing compound of coal, was utilized to explore nitrogen transformation during supercritical water gasification. Experiments were conducted with K2 CO3 as catalyst under temperature conditions from 650 °C to 750 °C, pressure of 25 MPa, and residence time from 1 min to 30 min with feedstock concentration of 2 wt%; products and nitrogen transformation characteristics were then investigated in detail. First, we found that carbon gasification efficiency of 95.89% was obtained under conditions of 750 °C, 25 MPa for 30 min, and that gaseous products mainly contained H2, CO, CO2 and CH4 . Nitrogen-containing products were not detected in gaseous products. Second, the main liquid intermediate organic products were phenol, aniline, and other nitrogen-containing compounds, and the liquid inorganic product was ammonia. Then a reaction pathway of indole gasification in supercritical water was proposed. The quantitative kinetic model for describing the gaseous products and nitrogen transformation mechanisms of indole was developed. The activation energy of carbon gasification reaction with K2 CO3 as catalyst was 209.1 ± 33.2 kJ/mol. Highlights: The experiments of indole gasification in supercritical water (SCW) were carried out. Products of indole gasification in SCW were measured. A nitrogen transformation pathway of indole gasification in SCW was proposed. A quantitative kinetic model for describing indole gasification in SCW was developed.